Electrocardiographic markers of incident atrial fibrillation in patients with cryptogenic stroke. (24th May 2021) - Couto Pereira, S; Silverio Antonio, P; Valente Silva, B; Brito, J; Rodrigues, T; Alves Da Silva, P; Veiga, A; Ferro, J; Pinto, FJ; Fonseca, C; Almeida, AG
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Prolonged screening of AF in patients (pts) with cryptogenic stroke (CS) is recommended and electrocardiographic markers of atrial remodeling, like p-wave dispersion, have been described in literature. Electrocardiographic changes in pts with CS to predict AF in the follow up are not well-established. Purpose: To identify ECG predictors of AF in a subset of pts with cryptogenic stroke. Methods: We prospectively included consecutive pts admitted with CS. A surface 12-lead ECG was performed at admission, recorded at 25 mm/second and 10 mV/cm with commercially available imaging system. P-wave analysis of maximum (P max) and minimum (P min) duration, p-wave dispersion (PWD, defined as the difference between the P max and P min, being abnormal if > 40 msec) and amplitude were evaluated by a two independent operator. P-wave axis was determined by an automated mode available in the equipment. ROC curve was analyzed to determine the optimal cut-off values. Results: We enrolled 105 pts (55.2% males), with mean age of 68.18 ± 8.83 years, 79% had hypertension, 18.1% had diabetes, 44.8% with dyslipidemia, 21% current smokers. During follow up period, 18 pts (17.1%) developed AF. We found that only PWD (AUC 0.706, IC95%: 0.564-0.848, p = 0.006) and P-wave axis (AUC 0.715, IC95%: 0.870-0.860, p = 0.004) were strong predictors of AF. PWD cut-off of 47.50 presented a sensitivity of 77.8% and specificity of 59.8% and P-wave axis cut off value of 75.50 had a specificity of 95.4%. Age (p = 0.032) and current smoking (p = 0.014) were associated with occurrence of AF during the follow up.   Conclusion: PWD and P-wave axis predicted incident AF in this subset of pts with cryptogenic stroke. The ECG may be a toll to identify pts at risk of developing AF, although larger studies are needed to confirm these results.